2011
DOI: 10.3390/molecules16043037
|View full text |Cite
|
Sign up to set email alerts
|

An Antimicrobial Compound Isolated from Cinnamomum Iners Leaves with Activity against Methicillin-Resistant Staphylococcus Aureus

Abstract: This study was designed to investigate the antimicrobial activity of Cinnamomum iners standardized leave methanolic extract (CSLE), its fractions and isolated compounds. CSLE and fractions were subjected to disc diffusion, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests using different Gram positive and Gram negative bacteria and yeast. Within the series of fractions tested, the ethyl acetate fraction was the most active, particularly against methicillin resistant Stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
1
15
0
3
Order By: Relevance
“…The strong antioxidant activity of the rhizome oil of C. xanthorrhiza may be related to the high level of xanthorrhizol (32%), although other constituents may also contribute to the antioxidant activity of the oil (Table 3). Previous studies have indicated that xanthorrhizol strongly inhibited platelet aggregation induced by arachidonic acid, collagen, and ADP [25] and had antimicrobial activity against Candida species, filamentous fungi and food-borne pathogens, Staphylococcus aureus and methicillin-resistant Staphylococcus aureus, (MRSA) [26, 27]. It also nonselectively inhibited DNA, RNA, and protein synthesis and exhibited antiproliferative activity on different cancer cell lines [28].…”
Section: Resultsmentioning
confidence: 99%
“…The strong antioxidant activity of the rhizome oil of C. xanthorrhiza may be related to the high level of xanthorrhizol (32%), although other constituents may also contribute to the antioxidant activity of the oil (Table 3). Previous studies have indicated that xanthorrhizol strongly inhibited platelet aggregation induced by arachidonic acid, collagen, and ADP [25] and had antimicrobial activity against Candida species, filamentous fungi and food-borne pathogens, Staphylococcus aureus and methicillin-resistant Staphylococcus aureus, (MRSA) [26, 27]. It also nonselectively inhibited DNA, RNA, and protein synthesis and exhibited antiproliferative activity on different cancer cell lines [28].…”
Section: Resultsmentioning
confidence: 99%
“…29 Hexadecanoic acid is also has the same properties as explained above, based on Duke's Phytochemical and Ethnobotanical Database and Jim Duke Agricultural Research Service/ USDA. 30 Phytochemical compound of 9-octadecenoic acid, methyl esters have been reported as Antibacterial and antifungal. 28 Based on the potent activity of the phytocompound, the antioxidant and antimicrobial activity shown by ethyl acetate extracts were mostly due to the content of hexadecanoic acids and their ester form.…”
Section: Resultsmentioning
confidence: 99%
“…Leaves of C. iners contain essential oils such as eugenol and cinnamaldehyde as major bioactive compounds (Jantan et al 1992). Reports have shown antimicrobial activities of essential oils from Cinnamomum species (Jantan et al 1992, Ranasinghe et al 2002, Mustaffa et al 2011. Antifungal tests demonstrated that cinnamaldehyde and eugenol had strong inhibitory effect against wood decay fungi (Wang et al 2005, Cheng et al 2006, while Yen & Chang (2008) concluded that the synergy of cinnamaldehyde with eugenol could alter cell wall structure of fungi, reduce cell wall synthesis, and the addition of radical scavenging.…”
Section: Diversity Of Saprobic Fungi On Magnolia Liliifera and Cinnammentioning
confidence: 99%